Subnational Debt Management Performance Assessment : Ogun State, Nigeria - World Bank (World Bank, Washington, DC, 2020)
At the request of the authorities, a World Bank (WB) subnational debt management performance assessment (SN-DeMPA) mission visited Ogun state, Nigeria between April 8 to 12, 2019. The main objective of the mission was to assess, jointly with the authorities, the current debt management performance of Ogun state. To meet this objective, the team worked closely with the debt management department (DMD) and met with other relevant state agencies and departments involved in public debt management. The SN-DeMPA observed several debt management functions that may benefit from improvements to meet the minimum effectiveness in DeM.